Membaca Reog Ponorogo di Media Sosial: Analisis Resepsi Generasi Z terhadap Konten Instagram @Reyogchestra - Iqbal Aria Bima; Rocky Prasetyo Jati (KOLONI, 2026)
This article analyzes Generation Z’s reception of Reog Ponorogo content on the Instagram account @Reyogchestra using Stuart Hall’s encoding/decoding model. The study adopts a qualitative approach within a constructivist paradigm. Data were collected through in-depth interviews with ten Generation Z informants aged 18–24, consisting of five followers and five non-followers of @Reyogchestra. The informants were exposed to three content stimuli: a video of a Reog performance in Taiwan, a large-scale national Reog performance video, and an infographic on various cultural traditions in Ponorogo. The data were analyzed using Braun and Clarke’s thematic analysis and Stuart Hall’s reception analysis to identify dominant-hegemonic, negotiated, and oppositional reading positions. The findings indicate that most informants occupy a dominant-hegemonic position in interpreting Reog as a proud, distinctive, and digitally relevant cultural identity. Negotiated readings mainly emerge in relation to the depth of educational information and the quality of content presentation, while oppositional readings are selective and limited to technical aspects of content production rather than rejection of Reog’s cultural values. The study reveals that Generation Z’s reception of digital cultural content is shaped by cultural nationalism framing, visual production quality, content format, and repeated exposure through the following mechanism. This article argues that the effectiveness of cultural communication on social media is determined not only by message content, but also by the aesthetic quality and strategic presentation of the message.